Testing the Associations among Social Axioms, School Belonging, and Flourishing in University Students: A Two‐Year Longitudinal Study. Issue 3 (24th June 2020) - Li, Yun; Tong, Kwok Kit; Tao, Vivienne Y. K.; Zhang, Meng Xuan; Wu, Anise M. S.
Abstract : Background: This longitudinal study investigated the temporal stability of social axioms, which are generalised social beliefs, and tested their prospective effects on individuals' flourishing, among students, as well as the extent to which they can be potentially mediated by perceived sense of belonging at school. Methods: Participants were 195 Chinese university students, who voluntarily completed a questionnaire measuring social axioms (at baseline, 1‐year follow‐up, and 2‐year follow‐up studies), school belonging (at 1‐year follow‐up study), and flourishing (at baseline and 2‐year follow‐up studies). Results: Results showed supportive evidence for five types of social axioms being generally stable across these time intervals. After controlling for baseline flourishing, high baseline social cynicism significantly predicted a lower level of follow‐up flourishing, whereas high baseline reward for application predicted a higher level of follow‐up flourishing. Furthermore, higher levels of social cynicism predicted lower levels of school belonging, and the latter partially mediated the effect of social cynicism on follow‐up flourishing. Conclusions: All social axioms are relatively stable across time. Social cynicism, reward for applications, and school belonging are the most salient predictors for flourishing among Chinese university students.